Analisis Resepsi Kelompok Pemilih Pemula Pemilu 2024 terhadap Iklan Politik Audiovisual Partai Amanat Nasional (PAN) - Faisal Haris; Azwar Azwar (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2024)
This research examines the audiovisual political advertisements of the National Mandate Party (PAN), specifically the jingle versions broadcasted through television and online platforms such as YouTube, in facing the Indonesia electoral contest 2024. The author focuses on the political message content and gimmicks that PAN, as the message producer, presents to the audience as message consumers in these advertisements. The aim of this study is to elucidate how the audience, particularly first-time voters in the 2024 elections, perceive the content of PAN's political advertisements. The author employs a qualitative approach and utilizes Stuart Hall's encoding-decoding model of reception analysis to comprehend how the informants receive and interpret these advertisements. The research results yield three main interpretations of informants regarding the PAN's audiovisual political advertisement; as something unique, as a political advertisement full of gimmicks lacking ideas, and as a pragmatic political display. Additionally, the research found that several informants were distributed among three audience positions; dominant hegemonic, negotiation, and opposition. The differences in these positions are influenced by their backgrounds in knowledge, education, and life experiences.